High-temperature composite coating for high-speed air bearing gas foil and preparation method of high-temperature composite coating

By applying high-temperature composite coating on air bearing gas foil, the existing coatings are solved, and the performance degradation and insufficient adhesion of the existing coatings under high temperature and high stress conditions are achieved, the high-temperature stability and long life of the bearing are reduced, and friction is reduced. and wear.

CN119465148APending Publication Date: 2025-02-18LINGWEI ZHIQING (HUZHOU) TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411653120.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing air bearing coatings have problems such as degradation of performance, unevenness, thermal stress accumulation, insufficient adhesion and complex manufacturing processes under high temperature and high stress conditions, which affect the stability and life of the bearing.

Method used

High-temperature composite coating is used, the bottom layer is nickel-chromium alloy, the middle layer is nano-alumina reinforced titanium alloy, and the surface layer is zirconia or alumina. It is sprayed through vacuum plasma spraying or high-pressure cold spraying technology and undergoes high-temperature sintering treatment to ensure the coating Uniformity and adhesion.

Benefits of technology

Maintaining the stability of the coating in extremely high temperature environments, providing excellent thermal insulation and mechanical properties, extending the service life of the bearing, reducing friction and wear, and improving equipment reliability and return on investment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465148A_ABST
    Figure CN119465148A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature composite coating for a high-speed air bearing gas foil and a preparation method of the high-temperature composite coating. The bottom layer of the coating is a nickel-chromium alloy coating, the middle layer of the coating is a nanometer aluminum oxide reinforced titanium alloy coating, and the surface layer of the coating is a zirconium oxide or aluminum oxide coating. The high-temperature composite coating disclosed by the invention can be kept stable in an extremely high-temperature environment, and excellent heat insulation performance is provided. The nanometer aluminum oxide reinforced titanium alloy in the middle layer provides good mechanical performance and enhances the impact resistance and abrasion resistance of the coating, the nickel-chromium alloy in the bottom layer provides good adhesive force and corrosion resistance and ensures firm combination of the coating and a base material, and the surface layer further improves the high temperature resistance and heat insulation performance of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of air bearings, and in particular relates to a high-temperature composite coating for a high-speed air bearing gas foil and a preparation method thereof. Background Art

[0002] Foil type gas powered gas film journal bearings are currently being used in various high speed rotor applications such as air compressors, small turbine generators, etc. These bearings consist of an internal rotating shaft, a non-rotating flexible gas foil surrounding the rotating shaft, a non-rotating flexible spring foil surrounding the gas foil, and a non-rotating bearing sleeve surrounding and providing fixation for the foil.

[0003] Gas foils are usually etched from a nickel alloy and rolled to final thickness. Spring foils are etched from Inconel that has been fully heat treated. Etched gas foils are typically coated with a low friction coating to reduce starting torque and to avoid damage to the foil from occasional contact during high RPM operation.

[0004] However, the existing coatings still have the following technical problems and defects that need to be solved urgently:

[0005] 1. Coating material selection and performance limitations: High-temperature coating materials need to remain stable under high temperature and high stress conditions, which places strict requirements on the selection of materials. The performance of currently commonly used coating materials such as oxide ceramics and metal coatings under extreme conditions still needs to be improved. Wear resistance and corrosion resistance: The coating needs to have excellent wear resistance and corrosion resistance at the same time. However, the existing coating materials may rapidly degrade in performance during long-term use, especially when exposed to a corrosive environment combining high temperature and chemical corrosion, and cannot meet the service life requirements of the equipment.

[0006] 2. Coating thickness and uniformity control: Coating thickness and uniformity have a great impact on bearing performance. Uneven coating may cause increased local wear and affect the stability and life of the bearing. In addition, too thin coating thickness will reduce the protective effect, while too thick coating thickness may affect the dynamic balance of the bearing.

[0007] 3. Thermal stress and coating peeling: Under ultra-high speed operation and high temperature environment, the difference in thermal expansion coefficient between the coating and the substrate may lead to thermal stress accumulation, which in turn leads to coating peeling. Coating peeling not only reduces the protective effect, but may also cause bearing failure.

[0008] 4. Adhesion between coating and substrate: Inadequate adhesion between coating and substrate material is a key issue. Good adhesion is essential for the durability of coating, but under high temperature and high stress conditions, the coating may peel or crack.

[0009] 5. Manufacturing and application process: The manufacturing and application process of the coating is complex, requiring high-precision equipment and strict process control. Improper process will lead to coating defects such as pores and cracks, affecting its performance and life. Summary of the invention

[0010] In view of the problems existing in the prior art, the purpose of the present invention is to provide a high-temperature composite coating for high-speed air bearing gas foil and a preparation method thereof. The high-temperature composite coating of the present invention can remain stable in extremely high temperature environments and provide excellent thermal insulation performance. The nano-alumina reinforced titanium alloy in the middle layer provides good mechanical properties and enhances the impact resistance and wear resistance of the coating. The nickel-chromium alloy in the bottom layer provides good adhesion and corrosion resistance, ensuring a firm bond between the coating and the substrate. The surface layer further improves the high temperature resistance and thermal insulation performance of the coating.

[0011] To achieve the above objectives, the present invention provides the following technical solutions:

[0012] A high-temperature composite coating for high-speed air bearing gas foil, the bottom layer of the coating is a nickel-chromium alloy coating, the middle layer is a nano-aluminum oxide reinforced titanium alloy coating, and the surface layer is a zirconium oxide or aluminum oxide coating.

[0013] Furthermore, the nickel (Ni) mass content of the nickel-chromium alloy coating is 75-85%, and the rest is chromium (Cr).

[0014] Furthermore, the mass content of nano-alumina in the nano-alumina reinforced titanium alloy coating is 5-10%, and the rest is titanium alloy; the titanium alloy is composed of 90% titanium (Ti), 6% aluminum (Al), and 4% vanadium (V).

[0015] Furthermore, the thickness of the bottom layer of the high-temperature composite coating is 10-30 μm, the thickness of the middle layer is 50-70 μm, and the thickness of the surface layer is 30-60 μm.

[0016] The present invention also provides a method for preparing the high-temperature composite coating for a high-speed air bearing gas foil, comprising the following steps:

[0017] (1) Cleaning and surface roughening the gas foil substrate in sequence;

[0018] (2) spraying nickel-chromium alloy powder on the pretreated substrate surface by vacuum plasma spraying or high-pressure cold spraying, and then performing high-temperature sintering to obtain a base layer;

[0019] (3) coating the surface of the substrate coated with the base layer with an ethanol solution containing nano-alumina and titanium alloy by spraying or brushing, and then drying and high-temperature sintering to obtain an intermediate layer;

[0020] (4) Plasma spraying technology is used to coat zirconium oxide or aluminum oxide powder on the surface of the intermediate layer, and then high-temperature sintering is performed to obtain a high-temperature composite coating.

[0021] Furthermore, the temperature of the high temperature sintering in step (1) is 500-600° C., and the heat preservation time is 1-2 hours.

[0022] Furthermore, the ethanol solution in step (2) also contains a dispersant and a binder; the sintering temperature is 400-500° C., and the insulation time is 1-2 hours.

[0023] Preferably, the dispersant is polyvinyl alcohol, and the binder is a silane coupling agent.

[0024] Furthermore, the temperature of the high temperature sintering in step (3) is 700-800° C., and the holding time is 1-2 hours.

[0025] Furthermore, the preparation method further comprises step (5): surface treatment of the high temperature composite coating is performed by high-precision grinding and polishing, so that the roughness Ra of the high temperature composite coating is 0.1-0.2.

[0026] The beneficial effects of the present invention are:

[0027] 1. The ceramic surface layer of the high-temperature composite coating of the present invention can remain stable in extremely high temperature environments and provide excellent thermal insulation performance. The nano-alumina reinforced titanium alloy in the middle layer provides good mechanical properties and enhances the impact resistance and wear resistance of the coating. The nickel-chromium alloy in the bottom layer provides good adhesion and corrosion resistance, ensuring a firm bond between the coating and the substrate.

[0028] 2. The high temperature composite coating of the present invention allows the air bearing to withstand higher temperatures, which is critical for the efficient operation of the micro gas turbine, especially when the ambient temperature is high or the temperature inside the system is high. The advanced composite coating of the present invention can enable the air bearing to operate at temperatures exceeding 800°C.

[0029] 3. The high-temperature composite coating of the present invention used for gas foil can significantly reduce friction and wear (bearing friction coefficient is reduced by 30% to 50%), improve the life and reliability of the bearing, and its service life is extended by 2-3 times compared with uncoated bearings, and it can work normally even under extremely harsh working conditions.

[0030] 4. The high-temperature composite coating of the present invention greatly reduces maintenance costs and operating costs, and improves the return on investment of the equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 These are scanning electron microscope photos of the high-temperature composite coating of Example 1; (a) scale is 20 microns; (b) scale is 10 microns. DETAILED DESCRIPTION

[0032] In order to make the technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. If the conditions are not clearly stated in the embodiments, they are carried out under normal conditions, and the instruments or reagents used are all commercially available.

[0033] Example 1

[0034] A method for preparing a high-temperature composite coating for a high-speed air bearing gas foil, wherein the bottom layer of the coating is a nickel-chromium alloy coating, the middle layer is a nano-alumina reinforced titanium alloy coating, and the surface layer is a zirconium oxide or aluminum oxide coating, comprising the following steps:

[0035] (1) The gas foil substrate is sequentially chemically cleaned or ultrasonically cleaned to remove oil, oxides and other impurities on the substrate surface, and then the surface is roughened by sandblasting or chemical etching to enhance the adhesion of subsequent coatings;

[0036] (2) spraying nickel-chromium alloy powder on the surface of the pretreated substrate by vacuum plasma spraying or high-pressure cold spraying, wherein the nickel (Ni) mass content is 75% and the rest is chromium (Cr), and then performing high-temperature sintering treatment at a temperature of 500° C. and a heat preservation time of 2 hours to obtain a bottom layer;

[0037] (3) dispersing nano-alumina Al2O3 (5%-15%wt) in ethanol, adding titanium alloy powder Ti6Al4V (70%-90%wt), and stirring evenly; adding a small amount of polyvinyl alcohol PVA (1%-5%wt) and silane (0.5%-1%wt) coupling agent, and continuing to stir to ensure uniform mixing; using a spraying or brushing method to apply the mixed solution on the surface of the substrate coated with the bottom layer; after coating, drying and sintering treatment are performed at a temperature of about 400°C for a holding time of 1 hour to obtain an intermediate layer, in which the mass content of nano-alumina is 5%, and the rest is titanium alloy; the titanium alloy is composed of 90% titanium (Ti), 6% aluminum (Al), and 4% vanadium (V);

[0038] (4) Zirconia or alumina powder is coated on the surface of the intermediate layer using plasma spraying technology, and then sintered at a high temperature of about 700°C for 1.5 hours to ensure the density and high temperature resistance of the surface layer;

[0039] (5) The coating is surface treated by high-precision grinding and polishing, so that the roughness Ra of the high-temperature composite coating is 0.1-0.2, thereby obtaining a high-temperature composite coating.

[0040] The cross-sections of the coatings were measured by scanning electron microscopy (SEM) to evaluate the uniformity and thickness of the coatings. Figure 1 The SEM scanning photo of the surface layer of the high-temperature composite coating is shown. The thickness of the bottom layer of the composite coating is 10-20μm, the thickness of the middle layer is 20-30μm, and the thickness of the surface layer is 30-50μm.

[0041] Example 2

[0042] A method for preparing a high-temperature composite coating for a high-speed air bearing gas foil, wherein the bottom layer of the coating is a nickel-chromium alloy coating, the middle layer is a nano-alumina reinforced titanium alloy coating, and the surface layer is a zirconium oxide or aluminum oxide coating, comprising the following steps:

[0043] (1) The gas foil substrate is sequentially chemically cleaned or ultrasonically cleaned to remove oil, oxides and other impurities on the substrate surface, and then the surface is roughened by sandblasting or chemical etching to enhance the adhesion of subsequent coatings;

[0044] (2) spraying nickel-chromium alloy powder on the surface of the pretreated substrate by vacuum plasma spraying or high-pressure cold spraying, wherein the nickel (Ni) mass content is 80% and the rest is chromium (Cr), and then performing high-temperature sintering treatment at a temperature of 500° C. and a heat preservation time of 1 hour to obtain a bottom layer;

[0045] (3) dispersing nano-alumina Al2O3 (5%-15%wt) in ethanol, adding titanium alloy powder Ti6Al4V (70%-90%wt), and stirring evenly; adding a small amount of polyvinyl alcohol PVA (1%-5%wt) and silane (0.5%-1%wt) coupling agent, and continuing to stir to ensure uniform mixing; using a spraying or brushing method to apply the mixed solution on the surface of the substrate coated with the bottom layer; after coating, drying and sintering treatment are performed at a temperature of about 500°C for a holding time of 2 hours to obtain an intermediate layer, in which the mass content of nano-alumina is 5%, and the rest is titanium alloy; the titanium alloy is composed of 90% titanium (Ti), 6% aluminum (Al), and 4% vanadium (V);

[0046] (4) Zirconia or alumina powder is coated on the surface of the intermediate layer using plasma spraying technology, and then sintered at a high temperature of about 800°C for 1 hour to ensure the density and high temperature resistance of the surface layer;

[0047] (5) The coating is surface treated by high-precision grinding and polishing, so that the roughness Ra of the high-temperature composite coating is 0.1-0.2, thereby obtaining a high-temperature composite coating.

[0048] Example 3

[0049] A method for preparing a high-temperature composite coating for a high-speed air bearing gas foil, wherein the bottom layer of the coating is a nickel-chromium alloy coating, the middle layer is a nano-alumina reinforced titanium alloy coating, and the surface layer is a zirconium oxide or aluminum oxide coating, comprising the following steps:

[0050] (1) The gas foil substrate is sequentially chemically cleaned or ultrasonically cleaned to remove oil, oxides and other impurities on the substrate surface, and then the surface is roughened by sandblasting or chemical etching to enhance the adhesion of subsequent coatings;

[0051] (2) spraying nickel-chromium alloy powder on the surface of the pretreated substrate by vacuum plasma spraying or high-pressure cold spraying, wherein the nickel (Ni) mass content is 85% and the rest is chromium (Cr), and then performing high-temperature sintering treatment at a temperature of 550° C. and a heat preservation time of 2 hours to obtain a bottom layer;

[0052] (3) dispersing nano-alumina Al2O3 (5%-15%wt) in ethanol, adding titanium alloy powder Ti6Al4V (70%-90%wt), and stirring evenly; adding a small amount of polyvinyl alcohol PVA (1%-5%wt) and silane (0.5%-1%wt) coupling agent, and continuing to stir to ensure uniform mixing; using a spraying or brushing method to apply the mixed solution on the surface of the substrate coated with the bottom layer; after coating, drying and sintering treatment are performed at a temperature of about 500°C for a holding time of 2 hours to obtain an intermediate layer, in which the mass content of nano-alumina is 5%, and the rest is titanium alloy; the titanium alloy is composed of 90% titanium (Ti), 6% aluminum (Al), and 4% vanadium (V);

[0053] (4) Zirconia or alumina powder is coated on the surface of the intermediate layer using plasma spraying technology, and then sintered at a high temperature of about 800°C for 1 hour to ensure the density and high temperature resistance of the surface layer;

[0054] (5) The coating is surface treated by high-precision grinding and polishing, so that the roughness Ra of the high-temperature composite coating is 0.1-0.2, thereby obtaining a high-temperature composite coating.

[0055] Example 4

[0056] A method for preparing a high-temperature composite coating for a high-speed air bearing gas foil, wherein the bottom layer of the coating is a nickel-chromium alloy coating, the middle layer is a nano-alumina reinforced titanium alloy coating, and the surface layer is a zirconium oxide or aluminum oxide coating, comprising the following steps:

[0057] (1) The gas foil substrate is sequentially chemically cleaned or ultrasonically cleaned to remove oil, oxides and other impurities on the substrate surface, and then the surface is roughened by sandblasting or chemical etching to enhance the adhesion of subsequent coatings;

[0058] (2) spraying nickel-chromium alloy powder on the surface of the pretreated substrate by vacuum plasma spraying or high-pressure cold spraying, wherein the nickel (Ni) mass content is 85% and the rest is chromium (Cr), and then performing high-temperature sintering treatment at a temperature of 500° C. and a heat preservation time of 1 hour to obtain a bottom layer;

[0059] (3) dispersing nano-alumina Al2O3 (5%-15%wt) in ethanol, adding titanium alloy powder Ti6Al4V (70%-90%wt), and stirring evenly; adding a small amount of polyvinyl alcohol PVA (1%-5%wt) and silane (0.5%-1%wt) coupling agent, and continuing to stir to ensure uniform mixing; using a spraying or brushing method to apply the mixed solution on the surface of the substrate coated with the bottom layer; after coating, drying and sintering treatment are performed at a temperature of about 450°C for a holding time of 1 hour to obtain an intermediate layer, in which the mass content of nano-alumina is 5%, and the rest is titanium alloy; the titanium alloy is composed of 90% titanium (Ti), 6% aluminum (Al), and 4% vanadium (V);

[0060] (4) Zirconia or alumina powder is coated on the surface of the intermediate layer using plasma spraying technology, and then sintered at a high temperature of about 750°C for 2 hours to ensure the density and high temperature resistance of the surface layer;

[0061] (5) The coating is surface treated by high-precision grinding and polishing, so that the roughness Ra of the high-temperature composite coating is 0.1-0.2, thereby obtaining a high-temperature composite coating.

[0062] The performance of the composite high-temperature coating obtained in the above-mentioned Examples 1 to 4 was tested, and the test results are shown in Table 1. Among them, the tensile test (pulling test) adopts the standard tensile method of GB 8641-1988 "Determination of tensile strength of thermal spray coatings" to measure the tensile strength of the coating; hardness: measured by a microhardness tester; thermal cycle temperature resistance: the coating is subjected to multiple thermal cycle tests (1000 cycles, from room temperature to 800°C) to evaluate the stability of the coating under repeated temperature changes.

[0063] Table 1 Performance test results of the composite high temperature coating obtained in Example 1-Example 4

[0064]

[0065] It can be seen from the above performance tests that the high temperature composite coating of the present invention has good adhesion, hardness, wear resistance and high temperature stability.

[0066] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high temperature composite coating for high speed air bearing gas foil, characterized in that: The bottom layer of the coating is a nickel-chromium alloy coating, the middle layer is a nano-aluminum oxide reinforced titanium alloy coating, and the surface layer is a zirconium oxide or aluminum oxide coating.

2. The high temperature composite coating according to claim 1, characterized in that: The nickel (Ni) mass content of the nickel-chromium alloy coating is 75-85%, and the rest is chromium (Cr).

3. The high temperature composite coating according to claim 1, characterized in that: The nano-aluminum oxide reinforced titanium alloy coating has a mass content of 5-10% of nano-aluminum oxide and the rest is titanium alloy; the titanium alloy consists of 90% of titanium (Ti), 6% of aluminum (Al), and 4% of vanadium (V).

4. The high temperature composite coating according to claim 1, characterized in that: The thickness of the bottom layer of the high-temperature composite coating is 10-30 μm, the thickness of the middle layer is 50-70 μm, and the thickness of the surface layer is 30-60 μm.

5. A method for preparing a high temperature composite coating for a high speed air bearing gas foil according to any one of claims 1 to 4, characterized in that: The steps include: (1) Cleaning and surface roughening the gas foil substrate in sequence; (2) spraying nickel-chromium alloy powder on the pretreated substrate surface by vacuum plasma spraying or high-pressure cold spraying, and then performing high-temperature sintering to obtain a base layer; (3) coating the surface of the substrate coated with the base layer with an ethanol solution containing nano-alumina and titanium alloy by spraying or brushing, and then drying and high-temperature sintering to obtain an intermediate layer; (4) Plasma spraying technology is used to coat zirconium oxide or aluminum oxide powder on the surface of the intermediate layer, and then high-temperature sintering is performed to obtain a high-temperature composite coating.

6. The preparation method according to claim 5, characterized in that: The temperature of the high-temperature sintering in step (1) is 500-600° C., and the insulation time is 1-2 hours.

7. The preparation method according to claim 5, characterized in that: The ethanol solution in step (2) also contains a dispersant and a binder; the sintering temperature is 400-500° C., and the insulation time is 1-2 hours.

8. The preparation method according to claim 7, characterized in that: The dispersant is polyvinyl alcohol, and the binder is a silane coupling agent.

9. The preparation method according to claim 5, characterized in that: The temperature of the high temperature sintering in step (3) is 700-800° C., and the insulation time is 1-2 hours.

10. The preparation method according to claim 5, characterized in that: The preparation method further comprises step (5): surface treatment of the high temperature composite coating is performed by high-precision grinding and polishing, so that the roughness Ra of the high temperature composite coating is 0.1-0.2.

Citation Information

Cited By

  • Niobium-vanadium-titanium microalloy seamless steel pipe and preparation method thereof

    CN121132209A